Colite necrohemorrágica causada por Entamoeba histolytica em um cão - Frade, Maria Talita Soares; Nascimento, Eduardo Melo; Olinda, Robério Gomes; Silva, Raquel Annes Fagundes; Oliveira, Fabrício Marcus Silva; Caliari, Marcelo Vidigal; Dantas, Antônio Flávio Medeiros (Acta Scientiae Veterinariae, 2017)
Background: Intestinal amebiasis with morphological lesions and clinical manifestations is uncommon in dogs. The disease is caused by the protozoan Entamoeba histolytica, which is commonly observed in its natural hosts, humans and some non-human primates. It is occasionally found in the company of animals, usually associated with contact with infected humans. Thus, the objective here is to describe a case of necro-hemorrhagic colitis caused by E. histolytica in a dog infected with the canine distemper virus, in order to characterize the epidemiological and clinicopathological aspects of the disease. Case: An adult, mixed-breed bitch displaying anorexia and ataxia was referred to the veterinary hospital for treatment. Clinical evaluation showed a cachectic animal with 12% dehydration, ocular discharge, and bilateral purulent nasal dis-charge. A clinical diagnosis of distemper was made, and treatment was instituted. The dog’s signs progressed to walking in circles, aimlessly, with lethargy and blindness. After three days of the onset of neurological signs, the dog developed diarrhea with hematochezia. With no improvement noted, we elected to euthanize the dog. At necropsy, edema was present in subcutaneous tissues, and the lungs had yellow areas in the cranio-ventral portions, which the court was flowing purulent discharge. In the large intestine, segmental distention of the distal portion of the descending colon was observed. The segment was approximately 15 cm in length and consisted of irregular reddish areas. There was also slight thickening of the wall with edematous mucosa containing blood clots, fibrin, and multiple areas of ulceration. Microscopically showed necro-hemorrhagic colitis associated with rounded structures, approximately 15 μm in size, containing abundant eosinophilic cytoplasm that was slightly granular or vacuolated. They also contained nuclei and nucleoli that were central or slightly eccentric. These organisms were consistent with amoeba trophozoites. There was also demyelinating encephalitis associated with malacia, corpuscular intranuclear eosinophilic inclusions and / or intracytoplasmic inclusions in ependymal cells, astrocytes, and gemistocytes, characteristic of infection with canine distemper virus. Using immunohistochemistry with polyclonal anti-E. histolytica antibodies in the dilution of 1:1000, trophozoites were immunomarked, confirming the suspected amebiasis. Discussion: The diagnosis of intestinal amebiasis was based on clinical signs and by morphological characteristics on gross and microscopic examination, and was confirmed as E. histolytica by immunohistochemistry. Limited information on the epidemiology and pathological findings of infection with Entamoeba sp. has been reported in the literature, as it is relatively uncommon in pets. Affected animals are usually asymptomatic, but immunosuppression caused by canine distemper virus may have triggered the clinical manifestations of the disease in this dog. Enteritis due Entamoeba sp. should be considered in dogs with chronic weight loss and bloody diarrhea. It should also be included in the differential diagnoses for weight loss and hemorrhagic gastroenteritis, such as canine parvovirus, canine adenovirus 1, Pythium insidiosum, and Giardia sp.